Effect of biochar coated potassium fertilizer on yield and nutritional value of maize - Bashir, Mafia; Sabah, Noor Us; Tahir, Mukkram Ali (Journal of Pure and Applied Agriculture, 2025)
Potassium (K) plays a critical function in the production of maize because it is essential to several physiological and biochemical processes that increase crop resilience and yield. A pot experiment on impact of biochar coated K on maize production was conducted in research area of university of Sargodha. The experiment was conducted in triplicate and comprised of 11 treatments. T1= control, T2= KCI @ 50 kg ha-1, T3 = K2SO4 @ 50 kg ha-1, T4 = KCI @ 50 kg ha-1 + 1 % BCM, T5 = KCI @ 50 kg ha-1 + 2 % BCM, T6 = K2SO4 @ 50 kg ha-1 + 1 % BCM, T7= K2SO4 @ 50 kg ha-1+ 2 % BCM, T8= KCI @ 25 kg ha-1 + 1 % BCM, T9= KCI @ 25 kg ha-1 + 2 % BCM, T10 = K2SO4 @ 25 kg ha-1 + 1 % BCM, T11= K2SO4 @ 25 kg ha-1 + 2 % BCM respectively. All treatments were applied two weeks after sowing. Results indicated that maximum K concentration was found where K was applied as K2SO4 @ 50 kg ha-1 + 2 % BCM. Thus, the mode of soil application of K had beneficial effect on nutritional composition of maize and yield.